Operational Monitoring Model of a Hermetic Cable Gland in NPP; Atomic Energy; Vol. 126, iss. 1 - Vashchuk S. P.; Deeva V. S. Vera Stepanovna; Kostyukov N. S.; Slobodyan S. M. Stepan Mikhaylovich (2019, 2019)
Title screen